2018
DOI: 10.1016/j.atherosclerosis.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Reduced calcification and osteogenic features in advanced atherosclerotic plaques of mice with macrophage-specific loss of TRPC3

Abstract: These findings show that, in advanced atherosclerosis, selective deletion of TRPC3 in macrophages favors plaque regression and impairs the activity of a novel macrophage-associated, BMP-2-dependent mechanism of calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Macrophage-specific TRPC3 deletion was sufficient to reduce atherosclerotic plaque in high fat diet-fed LDL receptor knockout VC rodent model. Furthermore, BMP2 as well as Runx2 expressing bone marrow derived macrophages was decreased in aortic root plaque [306]. This finding corroborates the importance of macrophage recruitment in VC.…”
Section: Inflammation and Immune Dysregulation In The Pathogenesis Ofsupporting
confidence: 81%
See 1 more Smart Citation
“…Macrophage-specific TRPC3 deletion was sufficient to reduce atherosclerotic plaque in high fat diet-fed LDL receptor knockout VC rodent model. Furthermore, BMP2 as well as Runx2 expressing bone marrow derived macrophages was decreased in aortic root plaque [306]. This finding corroborates the importance of macrophage recruitment in VC.…”
Section: Inflammation and Immune Dysregulation In The Pathogenesis Ofsupporting
confidence: 81%
“…A recent study highlights the role of transient receptor potential canonical 3 (TRPC3) in macrophage in VC [305][306][307]. TRPC3 deficiency reduces ER stress-induced apoptosis exclusively in M1 macrophages [305].…”
Section: Inflammation and Immune Dysregulation In The Pathogenesis Ofmentioning
confidence: 99%
“…Recently, the osteogenic genes expressed by macrophages have been intensively studied by many investigators. Dube et al demonstrated that selective deletion of TRPC3 (transient potential classical receptor 3, a nonselective calcium channel) in macrophages can reduce apoptosis of macrophages induced by endoplasmic reticulum stress and also attenuate the expression of BMP2 and Runx2 to reduce calcification in advanced atherosclerotic plaques (Dube et al, 2018). Nakano T also made use of the Delta-like 4 (DLL4) inhibitor, which can suppress the expression of BMP2 and Runx2 in macrophages to prevent the formation of vascular calcification via the Notch signaling pathway (Nakano et al, 2016).…”
Section: Functional Substances Secreted By Macrophagesmentioning
confidence: 99%
“…is the best characterized in innate immune cells 15 . TRPC3, was initially described to be involved in SOCE 16 .…”
Section: Introductionmentioning
confidence: 99%
“…TRPC3, together with TRPC6 and TRPC7, are calcium-permeable nonselective cation channels that share the special attribute of being activated by diacylglycerol (DAG) 13,14 . Of these, TRPC3 is the best characterized in innate immune cells 15 . TRPC3, was initially described to be involved in SOCE 16 .…”
Section: Introductionmentioning
confidence: 99%